Substrate, printed wiring board, and semiconductor package
By using a metal laminated plate with cured material of metal foil and prepreg on the substrate and laminated an insulating layer, the problem of large characteristic impedance fluctuations in the laminated plate substrate with a large thickness is solved, and more stable signal transmission is achieved.
Patent Information
- Application Number
- CN202480002353.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-19
- Filing Date
- 2024-05-31
- Publication Date
- 2025-02-21
AI Technical Summary
In substrates using laminated plates with large thickness, the fluctuations in characteristic impedance are large, making it difficult to meet the requirements of signal quality.
Using a metal laminated plate with a cured material of a metal foil and a prepreg, and an insulating layer is laminated thereon. The absolute value of the average thickness and thickness difference of the metal laminated plate is measured by a laser displacement meter to ensure that it is above 400 μm and The absolute value of the thickness difference is less than 10 μm.
It effectively reduces the characteristic impedance fluctuations of the substrate and improves signal quality, which is suitable for the high-speed and large-capacity needs of high-frequency signals.
Smart Images

Figure CN119498025A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a substrate, a printed circuit board and a semiconductor package. Background Art
[0002] The signals used in mobile communication devices such as mobile phones, their base station devices, network infrastructure devices such as servers and routers, and electronic devices such as large computers are becoming faster and larger year by year. In line with this, the substrate materials of printed circuit boards installed in these electronic devices need to suppress fluctuations in characteristic impedance in order to improve transmission characteristics.
[0003] Patent document 1 discloses a semi-cured synthetic resin sheet as a material for an insulating layer used in a multi-layer wiring substrate capable of easily achieving impedance integration of electronic components. The semi-cured synthetic resin sheet is characterized in that the semi-cured synthetic resin sheet used as a material for an insulating layer of a multi-layer wiring substrate contains cured synthetic resin spheres.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2002-141670 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, in recent years, the speed of signals has increased significantly, and in order to maintain signal quality, a higher control of characteristic impedance is required than before. In particular, according to the research of the inventors, it has been found that in substrates using thick laminates, the fluctuation of characteristic impedance tends to increase, and it is desired to improve it.
[0009] In view of such a current situation, the present embodiment aims to provide a substrate with less fluctuation in characteristic impedance, and a printed wiring board and a semiconductor package using the substrate.
[0010] Means for solving problems
[0011] The present inventors have conducted studies to solve the above-mentioned problems, and as a result, have found that the problems can be solved by the present embodiment described below.
[0012] [1] A substrate comprising:
[0013] A metal-clad laminate having a metal foil and a cured product of a prepreg; and
[0014] an insulating layer laminated on at least one surface of the metal-clad laminate,
[0015] The metal-clad laminate has an average thickness T1 of 400 μm or more measured by a laser displacement meter according to the following method, and an absolute value D1 of a difference between a maximum value and a minimum value of the thickness is 10 μm or less.
[0016] (Method for measuring average thickness T1 and absolute value D1 of difference between maximum and minimum thickness of metal-clad laminate)
[0017] In a plan view of the metal-clad laminate, four rectangular thickness measurement areas of 60 mm in length and 60 mm in width were set at arbitrary locations that did not overlap each other.
[0018] In the above rectangular thickness measurement area, 12 vertical measurement lines are set every 5 mm, starting from a position 2.5 mm away from the left side. On each vertical measurement line, the thickness is measured at intervals of 1 mm in the vertical direction, starting from a position less than 1 mm (but excluding 0 mm) away from the upper side.
[0019] In addition, in the rectangular thickness measurement area, 12 horizontal measurement lines are set every 5 mm, starting from a position 2.5 mm away from the upper side. On each horizontal measurement line, the thickness is measured at intervals of 1 mm in the horizontal direction, starting from a position less than 1 mm (but excluding 0 mm) away from the left side.
[0020] The absolute value of the difference between the maximum and minimum values of the thickness of the four thickness measurement areas is calculated, and the average value is set as the absolute value D1 of the difference between the maximum and minimum values of the thickness. In addition, the average thickness of all locations in the four thickness measurement areas is calculated and set as the average thickness T1 of the metal-clad laminate.
[0021] [2] The substrate according to [1], wherein the metal-clad laminate has metal foils on both surfaces, and one or more cured products of the prepreg are provided between the metal foils on the both surfaces.
[0022] [3] The substrate according to [1] or [2], wherein the metal-clad laminate comprises 2 to 20 sheets of cured products of the prepreg.
[0023] [4] The substrate according to any one of [1] to [3], wherein the prepreg is a prepreg comprising a fiber base material having a thickness of 40 μm or more and a thermosetting resin composition.
[0024] [5] The substrate according to any one of [1] to [4], wherein the insulating layer is laminated on both surfaces of the metal-clad laminate.
[0025] [6] The substrate according to any one of [1] to [5], wherein the insulating layer is a cured product of a film-like thermosetting resin composition.
[0026] [7] The substrate according to any one of [1] to [6], wherein the average thickness T2 of the insulating layer is 5 to 100 μm.
[0027] [8] A printed wiring board comprising the substrate described in any one of [1] to [7].
[0028] [9] A semiconductor package comprising the printed wiring board described in [8] above and a semiconductor element.
[0029] Effects of the Invention
[0030] According to the present embodiment, it is possible to provide a substrate having less fluctuation in characteristic impedance, and a printed wiring board and a semiconductor package using the substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 These are schematic diagrams for explaining a method for measuring the thickness of a metal-clad laminate ((a) and (b)).
[0032] Figure 2 This is a perspective view of an example of a measurement portion of a non-contact type and a clip-in type laser displacement meter used for measuring the thickness of a metal-clad laminate.
[0033] Figure 3 This is a schematic diagram of an example of a sensor head of a laser displacement meter used for measuring the thickness of a metal-clad laminate.
[0034] Figure 4 This is a schematic cross-sectional view showing one embodiment of a prepreg used in a metal-clad laminate.
[0035] Figure 5 This is a surface observation image obtained by converting the surface observation image used for calculation of the abundance ratio of the impregnation region in the prepreg produced in Example 1 into a surface observation image in a black-and-white mode.
[0036] Figure 6 This is a schematic diagram for explaining a method of determining thickness measurement areas ( N1 to N4 ) from predetermined locations at four corners of the metal-clad laminate when measuring the thickness of the metal-clad laminate in Examples and Comparative Examples. DETAILED DESCRIPTION
[0037] In the present specification, a numerical range expressed using "to" indicates a range including the numerical values described before and after "to" as the minimum value and the maximum value, respectively.
[0038] For example, a numerical range such as "X to Y" (X and Y are real numbers) means a numerical range of more than X and less than Y. In addition, the description "more than X" in this specification means X and a numerical value greater than X. In addition, the description "less than Y" in this specification means Y and a numerical value less than Y.
[0039] The lower limit value and the upper limit value of the numerical range described in the present specification can be arbitrarily combined with the lower limit value or the upper limit value of other numerical ranges, respectively.
[0040] In the numerical range described in the present specification, the lower limit value or the upper limit value of the numerical range may be replaced with the value shown in the Examples.
[0041] Each component and material exemplified in the present specification may be used alone or in combination of two or more unless otherwise specified.
[0042] In the present specification, when a plurality of substances corresponding to each component are present in the resin composition, the content of each component in the resin composition means the total amount of the plurality of substances present in the resin composition unless otherwise specified.
[0043] The term "solid content" as used herein refers to components other than the solvent, and components that are liquid at 25°C are also considered to be solid contents.
[0044] In this specification, "(meth)acrylate" means "acrylate" and its corresponding "methacrylate". Similarly, "(meth)acrylic" means "acrylic" and its corresponding "methacrylic", and "(meth)acryloyl" means "acryloyl" and its corresponding "methacryloyl".
[0045] The “semi-cured product” in this specification is synonymous with the resin composition in the B-stage state in JIS K 6800 (2006), and the “cured product” is synonymous with the resin composition in the C-stage state in JIS K 6800 (2006).
[0046] The action mechanism described in this specification is a guess, and does not limit the mechanism by which the effects of the present embodiment are achieved.
[0047] The present embodiment also includes any combination of the matters described in this specification.
[0048] [Substrate]
[0049] The substrate of this embodiment includes:
[0050] Metal-clad laminate having a cured product of metal foil and prepreg, and
[0051] an insulating layer laminated on at least one surface of the metal-clad laminate,
[0052] The metal-clad laminate has an average thickness T1 of 400 μm or more measured by the following method using a laser displacement meter, and an absolute value D1 of a difference between a maximum value and a minimum value of the thickness of the metal-clad laminate is 10 μm or less.
[0053] (Method for measuring average thickness T1 and absolute value D1 of difference between maximum and minimum thickness of metal-clad laminate)
[0054] In a plan view of the metal-clad laminate, four rectangular thickness measurement areas of 60 mm in length and 60 mm in width were set at arbitrary locations that did not overlap each other.
[0055] In the above rectangular thickness measurement area, 12 vertical measurement lines are set every 5 mm, starting from a position 2.5 mm away from the left side. On each vertical measurement line, the thickness is measured at intervals of 1 mm in the vertical direction, starting from a position less than 1 mm (but excluding 0 mm) away from the upper side.
[0056] In addition, in the rectangular thickness measurement area, 12 horizontal measurement lines are set every 5 mm, starting from a position 2.5 mm away from the upper side. On each horizontal measurement line, the thickness is measured at intervals of 1 mm in the horizontal direction, starting from a position less than 1 mm (but excluding 0 mm) away from the left side.
[0057] The absolute value of the difference between the maximum and minimum values of the thickness of the four thickness measurement areas is calculated, and the average value is set as the absolute value D1 of the difference between the maximum and minimum values of the thickness. In addition, the average thickness of all locations in the four thickness measurement areas is calculated and set as the average thickness T1 of the metal-clad laminate.
[0058] In addition, the "average" in the present embodiment means an arithmetic mean. In addition, the cured product of the prepreg means a cured prepreg.
[0059] The thickness of the metal-clad laminate can be determined, for example, by Figure 2 The non-contact and clip-in laser displacement meters shown in the figure measure the thickness by irradiating the object with laser light from both sides and detecting the distance between the surfaces with the reflected light.
[0060] More specifically, the thickness of the metal-clad laminate can be measured using the laser displacement meter and conditions described in the examples.
[0061] As described above, in the method for measuring the average thickness T1 and the absolute value D1 of the difference between the maximum and minimum thicknesses of the metal-clad laminate of the present embodiment, four rectangular thickness measurement areas of 60 mm in length and 60 mm in width are set.
[0062] On the other hand, in the case where four rectangular thickness measurement areas of 60 mm in length and 60 mm in width cannot be set due to the size of the metal-clad laminate, the thickness measurement area can be determined by the following method, and the average thickness of the metal-clad laminate and the absolute value of the difference between the maximum and minimum thickness values are calculated according to the above method based on the thickness measurement area. When the average thickness of the metal-clad laminate calculated by this method is 400 μm or more and the absolute value of the difference between the maximum and minimum thickness values is 10 μm or less, the same effect as the substrate of the present embodiment can be exerted. However, the lower limit of the thickness measurement area based on this method is 20 mm in length or more and 20 mm in width or more.
[0063] For example, in the case where only three or fewer rectangular thickness measurement areas of 60 mm in length and 60 mm in width can be set, the maximum number of rectangular thickness measurement areas of 60 mm in length and 60 mm in width that can be set is used as the measurement object. In addition, in the case where the dimension of the surface direction of the metal-clad laminate is a square less than 60 mm in length and less than 60 mm in width, it can be directly set as the thickness measurement area. In addition, in the case where the dimension of the surface direction of the metal-clad laminate is a rectangle less than 60 mm in length or less than 60 mm in width, the largest square that can be determined is set as the thickness measurement area. In the case where the thickness measurement area is less than 60 mm in length and width, the width of the measurement line is also set to the same as above, but the total number of measurement lines can be less than 12 according to the length of the length and width.
[0064] The preferred ranges of the average thickness of the metal-clad laminate and the absolute value of the difference between the maximum and minimum thicknesses calculated by the above method are the same as the preferred ranges of the average thickness T1 of the metal-clad laminate and the absolute value D1 of the difference between the maximum and minimum thicknesses of the substrate of the present embodiment.
[0065] <Metal-clad laminate>
[0066] The metal-clad laminate includes a metal foil and a cured product of a prepreg.
[0067] The metal-clad laminate has a metal foil on at least one surface, preferably on both surfaces, and has a cured product of one or more prepregs between the metal foils on the two surfaces. In addition, the metal-clad laminate may or may not have a metal foil on surfaces other than the two surfaces.
[0068] (Average thickness T1 of metal-clad laminate)
[0069] The average thickness T1 of the metal-clad laminate measured by the above-mentioned measurement method is 400 μm or more.
[0070] The substrate of this embodiment has an average thickness T1 of 400 μm or more, so the metal-clad laminate has sufficiently high rigidity when mounting a semiconductor chip, thereby suppressing warpage. Therefore, the substrate is suitable for use as a substrate for a particularly large semiconductor package.
[0071] From the above viewpoints, the average thickness T1 of the metal-clad laminate is preferably 500 μm or more, more preferably 700 μm or more, and even more preferably 1000 μm or more.
[0072] The average thickness T1 of the metal-clad laminate is preferably not thicker than necessary from the viewpoint of miniaturization and cost reduction, and is preferably 2500 μm or less, more preferably 2000 μm or less, and further preferably 1500 μm or less.
[0073] (Absolute value D1 of the difference between the maximum and minimum thickness of the metal-clad laminate)
[0074] The absolute value D1 of the difference between the maximum value and the minimum value of the thickness of the metal-clad laminate measured by the above-mentioned measuring method is 10 μm or less.
[0075] By setting the absolute value D1 of the difference between the maximum value and the minimum value of the thickness of the metal-clad laminate to 10 μm or less, the fluctuation in the characteristic impedance of the substrate of the present embodiment is reduced.
[0076] From the above viewpoints, the absolute value D1 of the difference between the maximum value and the minimum value of the thickness of the metal-clad laminate is preferably 8 μm or less, more preferably 6 μm or less, and even more preferably 5 μm or less.
[0077] The absolute value D1 of the difference between the maximum and minimum thicknesses of the metal-clad laminate is preferably as small as possible and may be 0 μm. However, from the viewpoint of ease of production, it may be 0.1 μm or more, 0.5 μm or more, or 1 μm or more.
[0078] (metal foil)
[0079] As the metal foil of the metal-clad laminate, copper foil, aluminum foil, tin foil, tin-lead alloy foil, nickel foil, etc. can be cited. In addition, three-layer composite foil with nickel, nickel-phosphorus, nickel-tin alloy, nickel-iron alloy, lead, lead-tin alloy, etc. as the intermediate layer, 0.5-15 μm copper layer and 10-300 μm copper layer on both sides, and two-layer composite foil obtained by combining aluminum and copper foil can also be cited. Among them, copper foil is preferred.
[0080] The thickness of the metal foil is preferably 1 to 200 μm, more preferably 2 to 100 μm, further preferably 3 to 50 μm, and particularly preferably 3 to 20 μm.
[0081] (Prepreg)
[0082] The prepreg preferably contains a fiber base material and a thermosetting resin composition.
[0083] The number of cured prepreg sheets in the metal-clad laminate may be appropriately determined depending on the application of the substrate, and may be, for example, 1 to 25 sheets, 2 to 20 sheets, 5 to 18 sheets, 8 to 16 sheets, or 10 to 14 sheets.
[0084] 〔Surface waviness of prepreg (Wa)〕
[0085] The surface waviness (Wa) of the prepreg is preferably 5.0 μm or less, more preferably 3.0 μm or less, and even more preferably 2.0 μm or less, from the viewpoint of reducing thickness fluctuation of the metal-clad laminate.
[0086] The lower limit of the surface waviness (Wa) of the prepreg is not particularly limited, and may be 0.01 μm or more, 0.1 μm or more, or 0.2 μm or more.
[0087] The surface waviness (Wa) is the arithmetic mean height (Wa) obtained from the waviness curve according to ISO 4287 (1997). Instead of ISO 4287 (1997), JIS B 0601 (2001) may be used. The surface waviness (Wa) can be measured as follows.
[0088] -Method for measuring the surface waviness (Wa) of prepregs-
[0089] Using a shape analysis laser microscope "VK-X100" (manufactured by Keyence Co., Ltd.), shape measurement is performed by automatic measurement using an observation application, and a waviness curve in accordance with ISO 4287 (1997) or JIS B 0601 (2001) is obtained. The obtained waviness curve can be subjected to surface roughness analysis using an analysis application to calculate the surface waviness (Wa). Here, the so-called waviness curve is a curve obtained by applying a phase compensation high-pass filter λc (λc = 80μm) to the cross-sectional curve and removing wavelengths less than 80μm from the above cross-sectional curve. In addition, the analysis range is set to 1000μm×1000μm.
[0090] It should be noted that, unless otherwise specified, the surface waviness (Wa) of a prepreg refers to the surface waviness of both surfaces of the prepreg.
[0091] [Unimpregnated area of prepreg]
[0092] From the viewpoint of reducing thickness fluctuations of the metal-clad laminate, the prepreg preferably has a region impregnated with the thermosetting resin composition and a region not impregnated in the fiber base material.
[0093] By forming the impregnation region and the non-impregnation region of the thermosetting resin composition in the fiber substrate, the surface waviness (Wa) of the prepreg tends to be reduced even when the thickness of the fiber substrate is large. Specifically, for example, even when a fiber substrate with a thickness of 40 μm or more is used, the surface waviness (Wa) tends to be suppressed to 5.0 μm or less.
[0094] The mechanism by which the above-mentioned effect is exerted is not certain, but it can be considered as follows.
[0095] Figure 4 : A schematic cross-sectional view of one embodiment of the prepreg 10 used in the metal-clad laminate is shown in FIG. By intentionally providing the unimpregnated region 3 in which the thermosetting resin composition 1 is not impregnated in the fiber base material 2 as in the prepreg 10, the layer of the thermosetting resin composition 1 near the surface (hereinafter also referred to as the "resin layer") does not follow the waviness of the fiber base material 2. It is considered that as a result, the large waviness of the fiber base material 2 is not easily reflected on the surface of the prepreg 10, and the surface waviness (Wa) of the prepreg 10 becomes small.
[0096] Even when the prepreg has unimpregnated regions, the thermosetting resin composition flows in the thickness direction and into the unimpregnated regions during press molding when manufacturing the metal-clad laminate, so that the generation of voids in the metal-clad laminate is sufficiently suppressed.
[0097] The presence of the unimpregnated region can be confirmed by determining the abundance ratio of the region impregnated with the thermosetting resin composition in the fiber base material. That is, if the abundance ratio of the impregnated region is not 100%, it means that there is an unimpregnated region.
[0098] The existence ratio of the impregnation region can be measured, for example, by the following measurement method. From the viewpoint of reducing thickness variation of the metal-clad laminate, the existence ratio of the impregnation region determined by the following method is preferably 20 to 99%, more preferably 30 to 98%, and even more preferably 50 to 95%.
[0099] -Method for measuring the impregnation area of prepreg-
[0100] The surface of the prepreg was observed using an optical microscope at a magnification of 50 times to obtain a surface observation image. The observation conditions were those described in detail in the examples from the viewpoint of capturing images with appropriate brightness.
[0101] The obtained surface observation image is converted to black and white mode using image editing software and saved in BMP (Microsoft Windows Bitmap Image) format. Then, the surface observation image in black and white mode saved in BMP format is converted into RGB (red, green, blue) values pixel by pixel using image conversion software and saved in CSV (comma-separated values) format. The RGB data saved in CSV format is pasted into Microsoft Excel (made by Microsoft Corporation) to calculate the area of the black part (RGB value = 255) and the white part (RGB value = 0). Based on these values, the area ratio of the black part relative to the total of the black part and the white part is calculated. The area ratio of the black part obtained in this way is set as the existence ratio of the impregnation area.
[0102] As the image editing software, for example, “Microsoft Paint” (manufactured by Microsoft Corporation) can be used. Also, as the image conversion software, for example, “bmp2csv” which is free software can be used.
[0103] It should be noted that in the above observation, if the surface observation image photographed at an appropriate brightness is converted to a black and white mode, the surface where the non-impregnated area of the thermosetting resin composition exists in the lower part of the observation surface is a void portion and is easy to reflect light, so it is displayed as "white", and the other surfaces are displayed as "black". Here, when photographing the surface observation image, in order to fully reflect the impregnation area and the non-impregnation area, the exposure time when photographing the surface is preferably adjusted in the range of 60 to 100 ms. For the surface observation image of the prepreg, in order from strong to weak color, it is "area where there is no glass cloth in the resin layer", "area where the thermosetting resin composition is fully impregnated in the glass cloth", and "area where the thermosetting resin composition is not sufficiently impregnated in the glass cloth". In this embodiment, "area where there is no glass cloth in the resin layer" is also included in the impregnation area. If the surface observation image is too bright, in the surface observation image in the black and white mode, not only the part where the resin is not sufficiently impregnated in the glass cloth is displayed as white, but also the part where the resin is fully impregnated in the glass cloth is easy to be displayed as white. When the image is brighter, the surface observation image in black and white mode tends to become white as a whole. On the other hand, if the surface observation image is too dark, the surface observation image in black and white mode tends to become black as a whole, and it tends to be difficult to reflect the existence of the unimpregnated area. Therefore, it is preferable to shoot at a moderate brightness. As an example of converting the surface observation image shot at a moderate brightness into a black and white mode, the surface observation image converted into a black and white mode obtained in Example 1 is shown in FIG. Figure 5 middle.
[0104] The area ratio of the white portion to the total area of the white portion and the black portion can be easily calculated by using the COUNTIF function of Microsoft Excel (manufactured by Microsoft Corporation).
[0105] 〔Thickness of prepreg〕
[0106] The thickness of the prepreg may be appropriately determined depending on the thickness of the fiber substrate and the like, and is preferably 50 to 300 μm, more preferably 60 to 200 μm, and even more preferably 70 to 150 μm.
[0107] The thickness of the prepreg is the thickness of one prepreg sheet. The thickness of the prepreg is the average value of values measured at five arbitrary points using a digital indicator.
[0108] [Thermosetting resin composition]
[0109] The thermosetting resin composition is not particularly limited as long as it contains a thermosetting resin.
[0110] -Thermosetting resin-
[0111] Examples of thermosetting resins include epoxy resins, polyimide resins, maleimide resins, modified maleimide resins, phenolic resins, polyphenylene oxide resins, bismaleimide triazine resins, cyanate resins, isocyanate resins, benzoxazine resins, oxetane resins, amino resins, unsaturated polyester resins, allyl resins, dicyclopentadiene resins, silicone resins, triazine resins, and melamine resins. Among them, epoxy resins, polyimide resins, maleimide resins, modified maleimide resins, and cyanate resins are preferred, and epoxy resins, maleimide resins, and modified maleimide resins are more preferred from the viewpoints of formability and electrical insulation.
[0112] The thermosetting resin may be used alone or in combination of two or more.
[0113] Examples of the modified maleimide resin include a reaction product of a maleimide resin having two or more N-substituted maleimide groups and one or more compounds selected from monoamine compounds and diamine compounds.
[0114] As the maleimide resin having two or more N-substituted maleimide groups, a bismaleimide resin having two N-substituted maleimide groups is preferred, and an aromatic bismaleimide resin having two N-substituted maleimide groups is more preferred.
[0115] As the monoamine compound, monoamine compounds having an acidic substituent such as aminophenol and aminobenzoic acid are preferred.
[0116] As the diamine compound, a diamine compound having two primary amino groups is preferred, and an aromatic diamine compound having two primary amino groups is more preferred.
[0117] As the epoxy resin, an epoxy resin having two or more epoxy groups in one molecule is preferred. Here, the epoxy resin can be classified into a glycidyl ether type epoxy resin, a glycidyl amine type epoxy resin, a glycidyl ester type epoxy resin, etc. Among them, a glycidyl ether type epoxy resin is preferred.
[0118] Epoxy resins can also be classified into various epoxy resins according to the difference of the main skeleton. For example, among the above-mentioned various types of epoxy resins, they can be further classified into bisphenol epoxy resins; alicyclic epoxy resins; aliphatic chain epoxy resins; novolac epoxy resins; stilbene epoxy resins; naphthalene skeleton-containing epoxy resins; biphenyl epoxy resins; xylene epoxy resins; dihydroanthracene epoxy resins, etc. Among them, naphthalene skeleton-containing epoxy resins are preferred from the viewpoint of insulation reliability and heat resistance.
[0119] The content of the thermosetting resin in the thermosetting resin composition is preferably 10 to 100% by mass, more preferably 20 to 80% by mass, and even more preferably 30 to 70% by mass, relative to the total solid content (100% by mass) of the thermosetting resin composition, from the viewpoint of heat resistance and moldability.
[0120] -Curing accelerator-
[0121] The thermosetting resin composition preferably further contains a curing accelerator.
[0122] As the curing accelerator, a common curing accelerator used when curing the thermosetting resin can be used. For example, when the thermosetting resin contains an epoxy resin, as the curing accelerator, imidazole compounds and derivatives thereof, phosphorus compounds, tertiary amine compounds, quaternary ammonium compounds, etc. can be cited. Among them, imidazole compounds and derivatives thereof are preferred from the viewpoint of promoting the curing reaction.
[0123] Examples of imidazole compounds and their derivatives include imidazole compounds such as 2-methylimidazole, 2-ethylimidazole, 2-undecylimidazole, 2-phenylimidazole, 1,2-dimethylimidazole, and 2,4-diamino-6-[2'-undecylimidazolyl-(1)']-ethyl-S-triazine; salts of the above imidazole compounds with trimellitic acid such as 1-cyanoethyl-2-phenylimidazolium trimellitic acid; salts of the above imidazole compounds with isocyanuric acid; and salts of the above imidazole compounds with hydrobromic acid. Among these, imidazole compounds are preferred, and 2,4-diamino-6-[2'-undecylimidazolyl-(1)']-ethyl-S-triazine is more preferred.
[0124] When the thermosetting resin composition contains a curing accelerator, the content of the curing accelerator in the thermosetting resin composition is preferably 0.01 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, and even more preferably 0.5 to 3 parts by mass relative to 100 parts by mass of the thermosetting resin, from the viewpoint of the curing acceleration effect and storage stability.
[0125] -Inorganic filler materials-
[0126] The thermosetting resin composition preferably further contains an inorganic filler.
[0127] Examples of the inorganic filler include silica, alumina, titanium oxide, mica, beryllium oxide, barium titanate, potassium titanate, strontium titanate, calcium titanate, aluminum carbonate, magnesium hydroxide, aluminum hydroxide, aluminum silicate, calcium carbonate, calcium silicate, magnesium silicate, silicon nitride, boron nitride, clay, talc, aluminum borate, silicon carbide, etc. Among them, silica, alumina, aluminum hydroxide, mica, and talc are preferred from the viewpoint of low thermal expansion, heat resistance, and flame retardancy, and silica and aluminum hydroxide are more preferred.
[0128] As silica, fused silica is preferred from the viewpoint of dispersibility and moldability.
[0129] The inorganic filler may be surface treated with a surface treatment agent such as a silane coupling agent to improve moisture resistance, or may be subjected to a hydrophobic treatment to improve dispersibility.
[0130] When the thermosetting resin composition contains an inorganic filler, the content of the inorganic filler in the thermosetting resin composition is preferably 10 to 90% by mass, more preferably 20 to 80% by mass, and even more preferably 30 to 70% by mass relative to the total solid content (100% by mass), from the viewpoint of low thermal expansion and moldability.
[0131] -Other ingredients-
[0132] The thermosetting resin composition may further contain other components such as resin materials, flame retardants, antioxidants, heat stabilizers, antistatic agents, ultraviolet absorbers, pigments, colorants, lubricants, organic solvents, and additives other than these components as needed.
[0133] The other components may be used alone or in combination of two or more.
[0134] The content of the other components in the thermosetting resin composition is not particularly limited, and may be used as needed in a range that does not inhibit the effects of the present embodiment.
[0135] In addition, the thermosetting resin composition may not contain the above-mentioned other components depending on the desired performance.
[0136] The thermosetting resin composition can be produced by mixing the components. In this case, the components can be dissolved or dispersed using an organic solvent while stirring as needed. The mixing order, temperature, time and other conditions are not particularly limited and can be arbitrarily set according to the types of raw materials.
[0137] 〔Fiber base material〕
[0138] As the fiber substrate contained in the prepreg, a known fiber substrate used in various laminates for electrical insulating materials can be used. As the material of the fiber substrate, natural fibers such as paper and cotton linters; inorganic fibers such as glass fibers and asbestos; organic fibers such as aramid, polyimide, polyvinyl alcohol, polyester, tetrafluoroethylene, acrylic fibers (acryl); mixtures thereof, etc. Among them, from the viewpoint of flame retardancy, inorganic fibers are preferred, and glass fibers are more preferred. As glass fibers, glass fibers using E glass, C glass, D glass, S glass, etc. can be mentioned.
[0139] The shape of the fiber substrate is not particularly limited, and may be woven fabric, nonwoven fabric, roving, chopped strand mat, surface mat, etc. Among them, woven fabric is preferred. That is, glass cloth is preferred as the fiber substrate.
[0140] The thickness of the fiber substrate is preferably 40 μm or more from the viewpoint of the handling properties of the prepreg. That is, the prepreg is preferably a prepreg containing a fiber substrate having a thickness of 40 μm or more and a thermosetting resin composition.
[0141] The thickness of the fiber substrate is preferably 60 μm or more, more preferably 70 μm or more, and particularly preferably 80 μm or more, from the same viewpoint as above. In addition, from the viewpoint of thinning the substrate, the thickness of the fiber substrate is preferably 120 μm or less, more preferably 110 μm or less, and further preferably 100 μm or less.
[0142] The surface waviness of the fiber substrate itself tends to increase as the thickness of the fiber substrate increases. However, by providing the impregnation region and the non-impregnation region in the prepreg as described above, the surface waviness (Wa) of the prepreg can be suppressed to a small value even when the thickness of the fiber substrate is 40 μm or more, and the thickness fluctuation of the metal-clad laminate can be reduced.
[0143] [Prepreg manufacturing method]
[0144] The method for producing the prepreg may be, for example, a method of laminating a film-shaped thermosetting resin composition (hereinafter also referred to as a "resin film") on a fiber base material (hereinafter also referred to as a "lamination method"), or a method of immersing the fiber base material in a thermosetting resin composition diluted with an organic solvent and then drying it (hereinafter also referred to as an "impregnation method"). Among these, the lamination method is preferred from the viewpoint of being easy to reduce the thickness fluctuation of the metal-clad laminate.
[0145] Next, the lamination method will be described.
[0146] The resin film used in the lamination method is preferably a resin film with a support having a support on one surface.
[0147] The resin film with a support can be produced, for example, by a method in which a varnish-like thermosetting resin composition (hereinafter also referred to as “resin varnish”) is applied to one surface of a support and then dried.
[0148] The resin varnish can be applied by using a known coating apparatus such as a comma coater, a bar coater, a kiss coater, a roll coater, a gravure coater, or a die coater.
[0149] The drying temperature and drying time after applying the resin varnish can be appropriately determined according to the type and amount of the organic solvent. For example, in the case of a resin varnish containing 30 to 70% by mass of an organic solvent, a resin film can be suitably formed by drying at 50 to 160° C. for 1 to 8 minutes.
[0150] The thickness of the resin film may be appropriately determined according to the thickness of the prepreg, and for example, when the thickness of the fiber substrate is 40 to 120 μm, the thickness of the resin film is preferably 10 to 100 μm, more preferably 15 to 70 μm, and even more preferably 20 to 50 μm.
[0151] Examples of the support include organic films such as polyethylene terephthalate (PET), biaxially oriented polypropylene (OPP), polyethylene, polyvinyl fluoride, and polyimide; and metal foils of metals such as copper and aluminum or alloys. These supports may be release-treated with a release agent.
[0152] The thickness of the support is, for example, 10 to 200 μm from the viewpoint of workability and economic efficiency when the thermosetting resin composition is applied.
[0153] The lamination of the resin film to the fiber substrate is performed as follows: first, the resin film with a support is arranged on at least one side of the fiber substrate in a direction such that the resin film and the fiber substrate are in contact. Then, the arranged resin film with a support and the fiber substrate are heated and pressurized, thereby impregnating the fiber substrate with the resin film. It should be noted that it is preferred to laminate the resin film with a support arranged on both sides of the fiber substrate.
[0154] Examples of the lamination method include (a) roll lamination and (b) lamination under reduced pressure.
[0155] When performing roll lamination (a), the heating temperature may be 80 to 180° C., or 100 to 150° C. The pressing pressure may be 0.05 to 1.0 MPa, or 0.2 to 0.6 MPa. The feeding speed may be 0.5 to 7.0 m / min, or 1.0 to 4.0 m / min.
[0156] (b) When laminating under reduced pressure, the heating temperature may be 80 to 180° C., or 100 to 150° C. In addition, the vacuum time may be 10 to 120 seconds, or 20 to 80 seconds. In addition, the pressurization time may be 10 to 120 seconds, or 20 to 80 seconds. In addition, the pressing pressure may be 0.05 to 1.0 MPa, or 0.1 to 0.6 MPa. The method of laminating under reduced pressure may be performed using a vacuum laminating apparatus.
[0157] As a method for providing a region not impregnated with the thermosetting resin composition in the fiber base material, for example, there can be mentioned a method of adjusting the conditions when heating and pressurizing the resin film with a support and the fiber base material.
[0158] Here, when the same lamination conditions are set when the fiber substrate is thin and when the fiber substrate is thick, there is a tendency that the resin film is not easily impregnated into the fiber substrate when the fiber substrate is thick. Therefore, even if the conditions for laminating a resin film on a thin fiber substrate in the past are the same as the lamination conditions of this embodiment, it is possible to provide a region not impregnated with the thermosetting resin composition in the fiber substrate in this embodiment.
[0159] As a specific method for adjusting the conditions for heating and pressurizing, for example, initially, after a prepreg is produced under predetermined heating and predetermined pressurizing conditions, the existence ratio of the impregnation region of the thermosetting resin composition in the fiber substrate based on the above calculation method is calculated. As a result, when the impregnation region is 100%, that is, when there is no unimpregnated region, the heating temperature or the pressurizing pressure is reduced, or both the heating temperature and the pressurizing pressure are reduced, and the prepreg is re-produced, and the existence ratio of the impregnation region is calculated again. The above operation is further repeated as needed, thereby making it easy to grasp the conditions for producing a prepreg having an unimpregnated region.
[0160] Furthermore, when it is desired to adjust the existence ratio of the unimpregnated regions to be lower, the prepreg may be re-made by increasing the heating temperature or the pressing pressure, or both the heating temperature and the pressing pressure.
[0161] In addition, when lamination is performed under reduced pressure, the existence ratio of the unimpregnated region can be adjusted by adjusting the vacuum degree.
[0162] (Method for producing metal-clad laminate)
[0163] The metal-clad laminate can be produced by a method in which a prepreg and a metal foil are stacked in order to form a desired structure and then press-molded.
[0164] The heating temperature during press molding is preferably 130 to 350°C, more preferably 150 to 300°C, and even more preferably 170 to 250°C.
[0165] The holding time at the maximum temperature during press molding is preferably 10 to 240 minutes, more preferably 30 to 180 minutes, and even more preferably 60 to 120 minutes.
[0166] The pressure of press-forming is preferably 0.5 to 10 MPa, more preferably 1 to 7 MPa, and even more preferably 2 to 5 MPa.
[0167] <Insulation layer>
[0168] The substrate of the present embodiment includes an insulating layer laminated on at least one surface of a metal-clad laminate.
[0169] The insulating layer is laminated on at least one surface of the metal-clad laminate, and preferably laminated on both surfaces of the metal-clad laminate.
[0170] The insulating layer may be a cured product of a prepreg or a cured product of a film-like thermosetting resin composition.
[0171] As the prepreg used as the insulating layer forming material, for example, the same prepreg as that used in the production of the metal-clad laminate can be used.
[0172] As the film-like thermosetting resin composition used as the insulating layer forming material, for example, the same thermosetting resin composition as the resin film used for producing the prepreg used for producing the metal-clad laminate can be used.
[0173] (Average thickness of insulating layer T2)
[0174] The average thickness T2 of the insulating layer is preferably 5 to 100 μm, more preferably 6 to 70 μm, and further preferably 8 to 50 μm.
[0175] When the average thickness T2 of the insulating layer is greater than or equal to the above lower limit, the insulating property tends to be more favorable. In addition, when the average thickness T2 of the insulating layer is less than or equal to the above upper limit, the substrate tends to be easily thinned.
[0176] The thickness of the insulating layer can be measured by the method described in Examples.
[0177] (Absolute value D2 of the difference between the maximum and minimum values of the thickness of the insulating layer)
[0178] The absolute value D2 of the difference between the maximum value and the minimum value of the thickness of the insulating layer is preferably 10 μm or less, more preferably 8 μm or less, and further preferably 6 μm or less.
[0179] When the absolute value D2 of the difference between the maximum value and the minimum value of the thickness of the insulating layer is equal to or greater than the lower limit, there is a tendency that the fluctuation of the characteristic impedance is likely to become smaller.
[0180] The absolute value D2 of the difference between the maximum and minimum values of the thickness of the insulating layer is preferably as small as possible and may be 0 μm. However, from the viewpoint of ease of manufacture, it may be 0.2 μm or more, 0.5 μm or more, or 1.0 μm or more.
[0181] The absolute value D2 of the difference between the maximum value and the minimum value of the thickness of the insulating layer can be measured by the method described in the examples.
[0182] <Method for manufacturing substrate>
[0183] The substrate of the present embodiment can be produced by laminating an insulating layer on at least one surface of a metal-clad laminate.
[0184] Specifically, for example, an insulating layer forming material is stacked on one or both surfaces of a metal-clad laminate, and metal foil is stacked on both outer sides as needed, and press molding is performed, thereby stacking an insulating layer on at least one surface of the metal-clad laminate.
[0185] As the metal foil, the same metal foil as that which can be included in the metal-clad laminate can be used.
[0186] The heating temperature during press molding is preferably 130 to 350°C, more preferably 150 to 300°C, and even more preferably 170 to 250°C.
[0187] The pressure of press-forming is preferably 0.5 to 10 MPa, more preferably 1 to 7 MPa, and even more preferably 2 to 5 MPa.
[0188] The pressurization time is preferably 10 to 240 minutes, more preferably 30 to 180 minutes, and even more preferably 60 to 120 minutes.
[0189] [Printed circuit board]
[0190] The printed wiring board of the present embodiment is a printed wiring board including the substrate of the present embodiment.
[0191] The printed wiring board of this embodiment can be manufactured by forming a conductor circuit on the substrate of this embodiment. The conductor circuit is preferably formed at least on the insulating layer of the substrate of this embodiment.
[0192] The conductor circuit can be formed by, for example, appropriately performing hole drilling, metal plating, etching of metal foil, etc. using a known method.
[0193] A multilayer printed wiring board can also be manufactured by performing a multilayer bonding process as needed.
[0194] [Semiconductor package]
[0195] The semiconductor package of the present embodiment is a semiconductor package including the printed wiring board of the present embodiment and a semiconductor element.
[0196] The semiconductor package of the present embodiment can be manufactured by, for example, mounting a semiconductor chip, a memory, and the like on a printed wiring board of the present embodiment by a known method.
[0197] Example
[0198] The present embodiment will be described in detail below with reference to examples, but the present embodiment is not limited to the following examples.
[0199] [Surface waviness (Wa)]
[0200] The shape of the prepreg produced in each example was measured by automatic measurement using a shape analysis laser microscope "VK-X100" (manufactured by Keyence Co., Ltd.) using an observation application, and a waviness curve in accordance with ISO 4287 (1997) was obtained. The obtained waviness curve was subjected to surface roughness analysis using an analysis application, and the surface waviness (Wa) of the prepreg was calculated. Here, the so-called waviness curve is a curve obtained by applying a phase compensation high-pass filter λc (λc = 80μm) to the cross-sectional curve and removing wavelengths less than 80μm from the cross-sectional curve. The analysis range was set to 1000μm×1000μm.
[0201] In addition, the surface waviness (Wa) was measured on both sides of the prepreg, and the larger value was adopted.
[0202] [Existence ratio of impregnation area]
[0203] The abundance ratio (%) of the region impregnated with the thermosetting resin composition in the fiber base material of the prepreg produced in each example was determined based on the following calculation method.
[0204] -Calculation method-
[0205] The surface of the prepreg was observed under the following conditions using an optical microscope (manufactured by Olympus Corporation, trade name: MX61L-F) to obtain a surface observation image.
[0206] <Observation conditions>
[0207] · Magnification: 50 times
[0208] Observation mode: dark field
[0209] Sensitivity: ISO400
[0210] Exposure time for surface photography: 60 to 100 ms
[0211] Brightness of the observation environment: Two 35W fluorescent lamps were installed 2m above the observation stage.
[0212] The obtained surface observation image is converted to black and white mode using image editing software and saved in BMP (Microsoft Windows Bitmap Image) format. Then, the surface observation image in black and white mode saved in BMP format is converted pixel by pixel into RGB (Red, Green, Blue) values using image conversion software and saved in CSV (comma-separated values) format. Paste the RGB data saved in CSV format into Microsoft Excel (made by Microsoft Corporation) to calculate the area of the black part (RGB value = 255) and the white part (RGB value = 0). Based on these values, the area ratio of the black part relative to the total of the black part and the white part is calculated. The area ratio of the black part obtained in this way is set as the existence ratio (%) of the impregnation area.
[0213] Here, when capturing the surface observation image, in order to adequately reflect the impregnated area and the non-impregnated area, the exposure time when capturing the surface is adjusted between 60 and 100 ms as described above, thereby capturing the image with appropriate brightness.
[0214] It should be noted that "Microsoft Paint" (manufactured by Microsoft Corporation) was used as the image editing software, and "bmp2csv" which is free software was used as the image conversion software.
[0215] [Method for measuring the average thickness T1 of the metal-clad laminate and the absolute value D1 of the difference between the maximum and minimum thicknesses of the metal-clad laminate]
[0216] From the four corners of the metal-clad laminate produced in each example (refer to Figure 6 ), in a plan view of the metal-clad laminate, a rectangular thickness measurement area (N1 to N4) of 60 mm in length and 60 mm in width was set.
[0217] Then, using the non-contact and clip-in laser displacement meter "CL-3000 series (sensor head: CL-L015)" (color laser coaxial displacement meter, Keyence Co., Ltd.), the thickness of the thickness measurement area (N1 to N4) was measured according to the following steps. It should be noted that the measurement conditions are as follows: measurement speed: 10 mm / sec, 1 measurement range: diameter 300 μm, resolution: 0.003 μm, repeatability 0.3 μm or less, sensor head size ( Figure 3 The repeatability refers to the degree of fluctuation when repeated measurements are made at a fixed point on the object to be measured. The smaller the repeatability, the smaller the degree of fluctuation of the value caused by repeated measurements.
[0218] First, if Figure 1 As shown in (a), in the rectangular thickness measurement area, 12 vertical measurement lines are set every 5 mm, starting from a position 2.5 mm away from the left side. Then, on each vertical measurement line, starting from a position less than 1 mm (but excluding 0 mm) away from the upper side, thickness measurement is performed at 1 mm intervals in the vertical direction.
[0219] Then, if Figure 1 As shown in (b), in the rectangular thickness measurement area, 12 horizontal measurement lines are set every 5 mm, starting from a position 2.5 mm away from the upper side. Then, on each horizontal measurement line, starting from a position less than 1 mm (but excluding 0 mm) away from the left side, the thickness measurement is performed at 1 mm intervals in the horizontal direction.
[0220] Thus, the thickness is measured at 1440 locations in each thickness measurement region (however, even if there are locations where the measurement sites overlap in the vertical and horizontal measurement lines, each is counted as one location).
[0221] Based on the thickness obtained by the above method, the absolute value of the difference between the maximum value and the minimum value of the thickness of the four thickness measurement areas (N1 to N4) is calculated, and the average is used as the absolute value D1 of the difference between the maximum value and the minimum value of the thickness of the metal-clad laminate. In addition, all the thicknesses obtained in the four thickness measurement areas (N1 to N4) are averaged, and the value obtained is used as the average thickness T1 of the metal-clad laminate.
[0222] [Method for measuring average thickness T2 of insulating layer and absolute value D2 of difference between maximum and minimum thickness of insulating layer]
[0223] The average thickness of the substrate and the absolute value of the difference between the maximum and minimum thickness of the substrate are calculated in the same manner as above, except that the measurement object is changed to the substrate obtained in each example in the above-mentioned [method for measuring the average thickness T1 of the metal-clad laminate and the absolute value D1 of the difference between the maximum and minimum thickness of the metal-clad laminate].
[0224] Then, the thickness of the insulating layer is calculated based on the following formula from the thickness of the substrate and the thickness of the metal-clad laminate at the same point.
[0225] Thickness of insulating layer = [Thickness of substrate - Thickness of metal-clad laminate - Thickness of copper foil] / 2
[0226] In addition, the "thickness of copper foil" in the above formula means the thickness of the copper foil laminated on the side of the insulating layer opposite to the metal-clad laminate.
[0227] Based on the thickness obtained by the above method, the average thickness T2 of the insulating layer and the absolute value D2 of the difference between the maximum value and the minimum value of the thickness of the insulating layer are calculated in the same procedure as in the case of the metal-clad laminate.
[0228] [Manufacturing of metal-clad laminated plates]
[0229] Production Example 1
[0230] <Manufacturing of Metal-Clad Laminated Plate 1>
[0231] (Preparation of modified maleimide resin)
[0232] Into a 2 L reaction container equipped with a thermometer, a stirrer, and a moisture meter with a reflux condenser and capable of heating and cooling, 595.8 g of bis(4-maleimidophenyl)methane, 54.2 g of 4,4'-diaminodiphenylmethane, and 350.0 g of propylene glycol monomethyl ether were added, and the mixture was reacted for 5 hours while reflux, thereby obtaining a solution of a modified maleimide resin (solid content concentration: 65% by mass).
[0233] (Production of resin varnish)
[0234] 107 parts by mass of the modified maleimide resin solution obtained above, 30 parts by mass of a tetrafunctional naphthalene epoxy resin "EXA-4710" (manufactured by DIC Corporation), 17.5 parts by mass of aluminum hydroxide and 130 parts by mass of fused silica, 0.5 parts by mass of 2,4-diamino-6-[2'-undecylimidazolyl-(1)']-ethyl-S-triazine, and methyl isobutyl ketone and cyclohexanone as diluents were added and mixed to prepare a resin varnish A having a solid content concentration of 65% by mass (aluminum hydroxide content: 8% by volume, fused silica content: 41.5% by volume).
[0235] (Production of resin film)
[0236] The resin varnish A obtained above was applied onto a PET film (manufactured by TORAY CO., LTD., thickness: 50 μm, trade name: S10) using a comma coater. At this time, the coating amount was adjusted so that the coating width was 530 mm and the thickness after drying was 30 μm. Thereafter, the varnish was dried by heating at 130° C. for 2 minutes, thereby producing a resin film with a PET film.
[0237] (Prepreg production)
[0238] In the glass cloth "IPC #2116" (made by Nitto Bosho Co., Ltd., basis weight: 104 g / m 2The resin film with the PET film is arranged on both sides of a substrate (with a width of 530 mm and a thickness of 91 μm) in contact with the glass cloth. The laminate of "PET film / resin film / glass cloth / resin film / PET film" is heated and pressurized under vacuum using a vacuum laminating device to obtain a prepreg with a PET film in which the glass cloth is impregnated with a thermosetting resin composition of the resin film. It should be noted that the conditions for vacuum lamination are set to a hot plate temperature of 130°C, a pressing pressure of 0.5 MPa, a vacuum degree of less than 100 kPa, a vacuum time of 30 seconds, and a heating time of 30 seconds. The PET film is peeled off from the obtained prepreg with a PET film to obtain prepreg 1 (thickness 125 μm, surface waviness (Wa) 0.5 μm, and the existence ratio of the impregnation area 62%).
[0239] The thickness of the prepreg was determined as the average value of the values measured at five arbitrary locations using a base adjusted to be horizontal and a digital indicator (manufactured by Mitutoyo Corporation).
[0240] The content ratio of the thermosetting resin composition in the prepreg 1 was calculated as follows. The mass of the resin film (w = 1 / 2) was calculated by subtracting the total mass of the two PET films from the total mass of the two PET films used to prepare the prepreg 1. r The mass of the resin film used (w r ) and the mass of prepreg 1 (w p ), the content ratio of the thermosetting resin composition is calculated using the following formula.
[0241] The content ratio of the thermosetting resin composition (mass %) = (w r / w p )×100
[0242] (Manufacturing of Metal-Clad Laminated Plates)
[0243] Twelve prepregs 1 obtained above were stacked, and copper foils "GTHMP-12" (manufactured by Furukawa Circuit Foil Taiwan of China Corporation) with a thickness of 12 μm were placed on the top and bottom. Then, the metal-clad laminated plate 1 was produced by pressing under the following conditions and cutting the end of the obtained metal-clad laminated plate to produce a rectangular metal-clad laminated plate 1 with a size of 500 mm×500 mm in plan view.
[0244] -Pressure conditions-
[0245] Heating conditions: heating from 25°C to 230°C at a heating rate of 3°C / min, maintaining at 230°C for 90 minutes, and cooling for 30 minutes.
[0246] Pressure conditions (pressure applied to 12 prepreg sheets sandwiched by copper foil): 4 MPa (from the start of heating to the end of cooling)
[0247] Production Example 2
[0248] <Manufacturing of Metal-Clad Laminated Plate 2>
[0249] Using the same steps as in Manufacturing Example 1, a laminate of "PET film / resin film / glass cloth / resin film / PET film" was prepared. Then, the laminate was heated and pressed using a pressure roller to obtain a prepreg with a PET film, in which the glass cloth was impregnated with a thermosetting resin composition with a resin film. It should be noted that the conditions of the pressure roller were set to a roller temperature of 130°C, a pressing pressure of 0.40 MPa, and a speed of 2.0 m / min. The PET film was peeled off from the obtained prepreg with a PET film to obtain Prepreg 2 (thickness 125 μm, surface waviness (Wa) 0.5 μm, and the existence ratio of the impregnation area 68%). It should be noted that the thickness of Prepreg 2 and the content ratio of the thermosetting resin composition were calculated in the same way as in Manufacturing Example 1.
[0250] Using the prepreg 2 obtained above, the same procedure as in Production Example 1 was followed to produce a metal-clad laminate 2 .
[0251] Production Example 3
[0252] <Manufacturing of Metal-Clad Laminated Plate 3>
[0253] The same glass cloth as that used in Manufacturing Example 1 was immersed in the resin varnish A prepared in Manufacturing Example 1, taken out, and dried by heating at 140° C. for 3.5 minutes to obtain a prepreg 3 (thickness 125 μm, surface waviness (Wa) 5.7 μm). Using this prepreg 3, a metal-clad laminate 3 was manufactured by the same steps as in Manufacturing Example 1.
[0254] [Manufacturing of substrates]
[0255] Examples 1 to 8, Comparative Examples 1 to 5
[0256] On the upper and lower sides of the metal-clad laminate of the type shown in Table 1, one sheet of resin film (manufactured by RESONAC Co., Ltd., trade name "AS-400HS", a resin film having an average thickness T2 of the insulating layer shown in Table 1) was overlapped, and further on both outer sides thereof, a copper foil with a thickness of 3 μm (manufactured by Mitsui Mining and Smelting Co., Ltd., trade name MT18FL, surface roughness Rz of the roughened surface: 1.3 μm) was overlapped, and press molding was performed under the conditions of a temperature of 230°C, a crimping pressure of 3.0 MPa, and a time of 80 minutes to obtain a metal-clad laminate with insulating layers laminated on both sides.
[0257] [Measurement of characteristic impedance]
[0258] The substrate obtained in each example was opened at the desired position, and a through hole was formed by electroless copper plating. Then, one side of the substrate was patterned by etching to form five microstrip lines with a line length of 50 mm, and a pattern for contacting a high-frequency probe was formed on one side of the signal line. The obtained substrate was used as a substrate for characteristic impedance measurement. It should be noted that the line width was designed in such a way that the characteristic impedance was 50Ω in consideration of the thickness of the insulating layer of each substrate.
[0259] The characteristic impedance was measured by connecting a high-frequency probe (Form Factor, trade name “ACP-65GSG-250”) and an oscilloscope equipped with a TDR module (Keysight Technology, trade name “54750A”, “54754A”) via a coaxial cable (HUBER-SUHNER, trade name “SUCOFLEX104”).
[0260] A high-frequency signal with a pulse rise time of 30 ps was injected from an oscilloscope, and a high-frequency probe was placed against the pattern of the characteristic impedance measurement substrate prepared above, and the characteristic impedance was calculated based on the measured voltage. The difference between the maximum and minimum values of the characteristic impedance of the 20 lines was defined as the fluctuation of the characteristic impedance (maximum value - minimum value). The results are shown in Table 1.
[0261] [Table 1]
[0262]
[0263] Table 1 shows that the substrates of Examples 1 to 8 of the present embodiment have small fluctuations in characteristic impedance. On the other hand, the substrates of Comparative Examples 1 to 5, in which the absolute value D1 of the difference between the maximum and minimum thicknesses of the metal-clad laminate is greater than 10 μm, have large fluctuations in characteristic impedance.
[0264] Description of Reference Numerals
[0265] 1 Thermosetting resin composition, 2 Fiber substrate, 3 Unimpregnated area, 10 Prepreg.
Claims
1. A substrate comprising: a metal-clad laminate having a metal foil and a cured product of a prepreg; and an insulating layer laminated on at least one surface of the metal-clad laminate, The metal-clad laminate has an average thickness T1 of 400 μm or more measured by a laser displacement meter according to the following method, and an absolute value D1 of a difference between a maximum value and a minimum value of the thickness is 10 μm or less. in, The average thickness T1 of the metal-clad laminate and the absolute value D1 of the difference between the maximum and minimum thicknesses are measured as follows: In a plan view of the metal-clad laminate, four rectangular thickness measurement areas of 60 mm in length and 60 mm in width were set at arbitrary locations that did not overlap each other; In the rectangular thickness measurement area, a position 2.5 mm away from the left side is used as a starting point, and longitudinal measurement lines are set every 5 mm, with a total of 12 lines set; on each longitudinal measurement line, a position less than 1 mm away from the upper side but not 0 mm is used as a starting point, and thickness measurement is performed at intervals of 1 mm in the longitudinal direction; In addition, in the rectangular thickness measurement area, a position 2.5 mm away from the upper side is used as a starting point, and horizontal measurement lines are set every 5 mm, and a total of 12 lines are set; on each horizontal measurement line, a position less than 1 mm away from the left side but not 0 mm is used as a starting point, and thickness measurement is performed at intervals of 1 mm in the horizontal direction; The absolute value of the difference between the maximum and minimum thicknesses in the four thickness measurement areas is calculated respectively, and the average value thereof is set as the absolute value D1 of the difference between the maximum and minimum thicknesses. Furthermore, the average thickness of all locations in the four thickness measurement areas is calculated and set as the average thickness T1 of the metal-clad laminate.
2. The substrate according to claim 1, wherein The metal-clad laminate has metal foils on both surfaces, and has one or more cured products of the prepreg between the metal foils on the both surfaces.
3. The substrate according to claim 1 or 2, wherein The metal-clad laminate includes 2 to 20 sheets of cured products of the prepreg.
4. The substrate according to claim 1 or 2, wherein The prepreg is a prepreg comprising a fiber base material having a thickness of 40 μm or more and a thermosetting resin composition.
5. The substrate according to claim 1 or 2, wherein The insulating layer is laminated on both surfaces of the metal-clad laminate.
6. The substrate according to claim 1 or 2, wherein: The insulating layer is a cured product of a film-like thermosetting resin composition.
7. The substrate according to claim 1 or 2, wherein: The average thickness T2 of the insulating layer is 5 μm to 100 μm.
8. A printed wiring board comprising the substrate according to claim 1 or 2.
9. A semiconductor package comprising the printed wiring board according to claim 8 and a semiconductor element.
Citation Information
Patent Citations
Half-setting synthetic resin sheet and its manufacturing method, and multi-layered wiring board
JP2002141670A